Boundary crossing and learning identities – digital storytelling in primary schools - Bjørgen, Anne Mette (Seminar.net, 2010)
This article contributes to academic discussions on how digital storytelling in an educational setting may have potential to build and develop learning identities, agency and digital competences. With a socio-cultural framework on learning and identity as a point of departure, the article sets out to study these issues approached as boundary crossing between the intersecting contexts of leisure time and school. The analysis draws on three examples of digital storytelling among 5th - 7th graders in three Norwegian primary school classes. My findings suggest that digital storytelling might represent a boundary crossing enabling pupils to adopt new roles as producers of creative content, as mentors or guides, to explore new technology and software in a context different from that of outside school and to learn and develop competences related to production processes and multimodal resources. I argue that digital storytelling has a potential to contribute to learning, learning identity and agency, provided it is based on a more fully developed pedagogical strategy of carefully linking school and leisure time.